2018
DOI: 10.3390/ijms19061734
|View full text |Cite
|
Sign up to set email alerts
|

ALUminating the Path of Atherosclerosis Progression: Chaos Theory Suggests a Role for Alu Repeats in the Development of Atherosclerotic Vascular Disease

Abstract: Atherosclerosis (ATH) and coronary artery disease (CAD) are chronic inflammatory diseases with an important genetic background; they derive from the cumulative effect of multiple common risk alleles, most of which are located in genomic noncoding regions. These complex diseases behave as nonlinear dynamical systems that show a high dependence on their initial conditions; thus, long-term predictions of disease progression are unreliable. One likely possibility is that the nonlinear nature of ATH could be depend… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 183 publications
(231 reference statements)
0
19
0
2
Order By: Relevance
“…ALU elements are a family of primate‐specific short interspersed repeat elements (SINEs) and are linked with AS through facilitating the adhesion and proliferation of mononuclear cells . The functional relevance of ALU motifs in ANRIL was confirmed by deletion . Hold et al found that ANRIL (with ALU elements) facilitated adhesion and proliferation of mononuclear cells, thus aggravating the development of AS (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ALU elements are a family of primate‐specific short interspersed repeat elements (SINEs) and are linked with AS through facilitating the adhesion and proliferation of mononuclear cells . The functional relevance of ALU motifs in ANRIL was confirmed by deletion . Hold et al found that ANRIL (with ALU elements) facilitated adhesion and proliferation of mononuclear cells, thus aggravating the development of AS (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…54,55 65 The functional relevance of ALU motifs in ANRIL was confirmed by deletion. 66,67 Hold et al 68 found that ANRIL (with ALU elements) facilitated adhesion and proliferation of mononuclear cells, thus aggravating the development of AS (Figure 3). which inhibited the AMPK/SIRT1 signalling pathway.…”
Section: Anril and Vascular Smooth Muscle Cellsmentioning
confidence: 99%
“…Atherosclerosis (ATH) is a complex inflammatory disease of the vessel wall caused by a combination of multiple factors including genomics, epigenetic modifications and environmental conditions, that place an enormous burden on modern societies, particularly in the aging population [1]. The complexity of its causes and mechanisms makes ATH prevention and treatment largely ineffective, becoming an enormous challenge for our society, favored by our lifestyle [2,3].…”
Section: Background Atherosclerosis Progression and The Dark Transcrmentioning
confidence: 99%
“…The injection of ApoExos containing unedited Alu repeats resulted in inflammation in mice (26). Alu had an influence on the inflammatory response mechanisms of atherosclerosis and coronary artery disease (53). The formation of NLRP3 inflammasome and upregulation of IL-18 and IL-1b subsequently were activated by the accumulation of Alu transcripts (36,37).…”
Section: Discussionmentioning
confidence: 99%